Differentiation, functions, and roles of T follicular regulatory cells in autoimmune diseases - He Hao; Shingo Nakayamada; Yoshiya Tanaka (BMC, 2021)
Abstract T follicular helper cells participate in stimulating germinal center (GC) formation and supporting B cell differentiation and autoantibody production. However, T follicular regulatory (Tfr) cells suppress B cell activation. Since changes in the number and functions of Tfr cells lead to dysregulated GC reaction and autoantibody response, targeting Tfr cells may benefit the treatment of autoimmune diseases. Differentiation of Tfr cells is a multistage and multifactorial process with various positive and negative regulators. Therefore, understanding the signals regulating Tfr cell generation is crucial for the development of targeted therapies. In this review, we discuss recent studies that have elucidated the roles of Tfr cells in autoimmune diseases and investigated the modulators of Tfr cell differentiation. Additionally, potential immunotherapies targeting Tfr cells are highlighted.